Fostering Global Citizenship through Religious Education: A Case Study Approach - Alisher Nasriddinov; Shakhnoza Yuldasheva; Bakhtiyor Rakhimov (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2025)
This research examines how religious education can be used to foster a sense of global citizenship among students. Through case studies from selected schools and interviews with educators, the study identifies specific pedagogical strategies that encourage students to engage with global issues from an ethical and intercultural perspective. The findings suggest that religious education, when integrated with discussions on global issues, can empower students to become active, empathetic, and socially responsible citizens.